MEDIATION ROLE OF WORK-LIFE BALANCE ON THE EFFECT OF JOB DEMAND AND WORKPLACE RESOURCES ON NURSE JOB SATISFACTION DURING THE COVID-19 PANDEMIC - Baisa, Quthrin Nada Machzum; Nilasari, B. Medina (Jurnal Aplikasi Manajemen, 2022)
The COVID-19 pandemic has become a critical concern for the health nursing industry, especially in the city of Jakarta, due to the very high population density of the city of Jakarta. This pandemic has placed a huge burden on nursing professionals as the frontlines deal directly with such a huge disaster. How can Workplace Resources combat the challenges of increasing Job Demands and provide a healthy Work-Life Balance? So that nurses get Job Satisfaction during this pandemic. This study aims to analyze the mediating role of Work-Life Balance on the effect of Job Demand and Workplace Resources on Job Satisfaction. The data used in this study is cross-sectional, namely data collected on selected respondents at a certain time. The research sample consisted of 301 nurses from eight hospitals in Jakarta who received covid-19 patients. The data analysis used for hypothesis testing was the Structural Equation Model (SEM) analysis with the help of SmartPLS 2.0 software. The results showed an effect of Job Demand and Workplace Resources on Work-Life Balance. There was an effect of Work-Life Balance on Job Satisfaction, and the Work-Life Balance variable was proven to mediate the effect of Job Demand and Workplace Resources on Job Satisfaction. Hospitals Management needs to calculate the maximum number of patients that nurses can handle and give them autonomy so they can make changes to work methods. Also, encourage nurse supervisors to help deal with stress in the workplace by maintaining a work-life balance. Nurses support nurse supervisors to provide recognition for nurses who perform well to increase job satisfaction.